CHARACTER EDUCATION IN ISLAMIC BOOK “ALALA” - Ni’am, Iqbal Akmalun (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Nowadays, there are several degradations moral which happen to children or even teenagers. Some examples of the degradations that happen are lack of affection toward children, no respect toward elders, being shiftless, no ambition in gaining knowledge, fleeing from school and even being impertinent to parents. These misbehavior has been spread among lives of children and teenagers widely. Those underline the reason of why the character building is very important in this life because this life has no advantage without virtue. I as the researcher, realize that there is needed an effort to be more aware of this situation by educating moral value to my students. The moral education is based on several bases such as peace, achievement, cooperation, helping each other, freedom, happiness, modesty, affection, responsibility, tolerance and unity. These aspect are influenced by several factors from both internal and external. The internal factor comes up from the human. In the other side, the external factor appears from education factor. There are many Islamic books that discuss  character building. As the example, there is an Islamic book entitled Alala written by Syaikh Abu Baasyir Romawi with descriptive qualitative method. I analyze the data with content analysis method. It is proven by existences of some morals that are religiously, honestly, tolerance, discipline, hard work, creative, independent, democratic, curious, appreciate of achievement, communicative, spirit to reading, social caring, responsibility. Moreover, the author also use uswah hasanah , story, conversation and advise to explain the kind of characters.